Implementasi Penyesuaian Obat Diabetes pada Saat Puasa Ramadan dan Pengaruhnya Terhadap Nilai HbA1c - Safyanty, Rahmi; Andrajati, Retnosari; Supardi, Sudibyo; Dewi Sartika, Ratu Ayu (Fakultas Farmasi Universitas Andalas, 2020)
This study aimed to evaluate the effect of diabetes medication adjustment during Ramadan fasting according to the recommendation of International Diabetes Federation-Diabetes and Ramadan International Alliance (IDF-DAR) to HbA1c values in type-2 diabetes mellitus patients. The study was conducted at a hospital in Jakarta, Indonesia with a cross-sectional study design involving 80 ambulatory patients with type-2 DM who fasted during Ramadan in 2016. About 60% of patients used oral antidiabetes drug (OAD), mostly the combination of biguanide + sulfonylurea drugs (27.5%). The adjustments were made in which 56.2% was in accordance with IDF-DAR recommendations. The study showed that the HbA1c values decreased insignificantly (p = 0.082) from 8.75 Â± 1.90 to 8.63 Â± 1.82 after the adjustment. The appropriate drug adjustment based on IDF-DAR had a significant effect on the HbA1c value of DM patient with p-value 0.030 (p < 0.05).The discrepancy of drug use based on IDF-DAR 3.222 times greater caused uncontrolled HbA1c. The most influential variable to HbA1c value was drug type with p-value 0.006 (p < 0.05). Improper adjustment of Insulin or combination insulin-OAD caused HbA1c value 5 times greater to be uncontrolled than OAD.